Development of E-Module on The Diversity of Living Things on Problem-Based-Learning (PBL) to Improve Students' Critical Thinking Skills. - Verdamil, Ainun Cornelia; Rohman, Fatchur; Susanto, Hendra; Wijiasih, Wijiasih; Robi, Fikri Syahir (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
An ineffective learning process can cause students’ critical thinking skills to be low. This study aims to develop an e-module for the diversity of living things based on problem-based-learning (PBL) in improving students’ critical thinking skills. Research and development model from Lee & Owen (assessment/analysis, development design, implementation, and evaluation). This research was conducted at MAN Kota Batu. The research population, namely all of tenth grade students in the school year of 2023, the sample used was 36 students with sampling techniques using non-probability by purposive sampling. The research design was one-group-pre test-post test to measure the critical thinking skills after using the e-module. Based on the results showed that the e-module developed was stated very valid (97, 25%), very practical based on students’ responses (91, 6%) and teachers’ responses (89%), and based on the N-gain score to see the effectiveness obtained a value of .6 which means that the students’ critical thinking skills developed in the medium category after the application of e-module based on Problem-based-learning.